Qishotu Âdam fî al-Qurân ‘Inda Muhamad ‘Abduh (Al-Dirâsat at-Tahlîliyah fî Sûrati al-Baqarah al-Âyat 30-39) - Ahmad Suharto; Urwatul Wustqo (Studia Quranika, 2019)
One of the unique stories in the al-Qur’an is the story of Adam as. Because in this story many things are mentioned disappear news that cannot be directly accepted by reason, Muhamad Abduh is one of the rationalist exegetical figures, he has a different thought of what is implied in the story of Adam, he saw that the story of Adam in Surat al-Baqarah verses 30-39 explained the flow of human life and human potential as a leader of this world. According to him, there were other creatures before Adam who lived on earth and Adam was not the first human. He also mentioned that the story of Adam as a symbolic story, it makes the story of Adam in the Koran not real. Based on that problems, the purpose of this study is to know the interpretation and opinion of Muhamad Abduh regarding human potential in Surat al-Baqoroh verses 30-39, this research used two methods. The first is descriptive method where the researcher will explain the explanation of the interpretation of Muhamad Abduh in Surat al-Baqoroh verses 30-39. The second is the analytical method where the researcher presented a little criticism about the interpretation of Muhamad Abduh then draws conclusions about Muhamad Abduh's interpretation of human potential in surat al -Baqarah verses 30-39.